Mobile sampling of methane emissions from natural gas well pads in California. (1st January 2021) - Zhou, Xiaochi; Yoon, Seungju; Mara, Steve; Falk, Matthias; Kuwayama, Toshihiro; Tran, Travis; Cheadle, Lucy; Nyarady, Jim; Croes, Bart; Scheehle, Elizabeth; Herner, Jorn D.; Vijayan, Abhilash
Abstract: The oil and natural gas sector is the second largest source of methane (CH4 ) emissions in the U.S. (28% in 2018), and several studies have suggested that real-world emissions from this sector may be higher than previously reported estimates. This study was designed to measure methane emissions from non-associated (i.e., produced without crude oil extraction) natural gas (NG) well pads in California, by applying a novel mobile measurement system combined with a source characterization model. This study surveyed 86 non-associated NG well pads (66 active and 20 idle well pads) in northern California during a two-week field campaign in 2018. The mean emission rate from active non-associated NG well pads was estimated to be 9.5 (95% CI: 6.1–14.6) kg CH4 /d. By extrapolating the survey results to the entire state, the annual methane emissions from all active non-associated NG well pads were 3.2 (95% CI: 2.0–5.1) Gg CH4 /y, which represents roughly 5% of CH4 emissions from the oil and natural gas production sector in California. The methane emission rates exhibited a fat-tail distribution, with roughly 15% of the active well pads responsible for >85% of the total measured emissions. This result suggests that controlling a small number of large emitters can significantly reduce methane emissions from this sub-sector. Methane emissions were also detected from over 60% of the idle well pads, with a similar fat-tail distribution but much smaller magnitudes than the active well pads. Quick screening tools to identify and fix these unexpected fugitive leaks can offer useful real-world emission reductions. The mobile measurement system was also able to detect emissions from more well pads when compared to the use of an optical gas imaging camera, which suggests that mobile measurement techniques can be an effective screening tool to support leak detection and repair (LDAR) programs. Highlights: A mobile measurement system was developed to screen and quantify methane emissions. Emissions from active non-associated NG well pads in California were measured. Averaged emissions rates are comparable to estimates based on emission factors. The sub-sector represents 5% of methane emissions from California O&G production.